2019 IEEE 6th International Conference on Energy Smart Systems (ESS) 2019
DOI: 10.1109/ess.2019.8764205
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Spectral Theory for Analysis of Non-Stationary Pulse Stochastic Electromagnetic Processes in Devices of Electric Transport Systems

Abstract: A spectral analysis of traction voltages and currents is a basis for estimation of electromagnetic compatibility level and quality of consumed power in electric transport systems. However, such an analysis is usually performed for steady-state modes and only under the condition that the time realization of voltages and currents, being deterministic for continuous quantities, have infinite length. De facto, the electric transport devices operate in non-stationary dynamic modes (starting up, coasting, accelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Example calculations of active losses in all conductive elements, not only in the conducting circuits (rails, catenary), showed that the proposed "field" approach to active losses is more complex and takes into account losses in locomotives and wagons. Another approach to electromagnetic processes in electric transport systems is presented in paper [25].…”
Section: Overview Of Contributions To This Special Issuementioning
confidence: 99%
“…Example calculations of active losses in all conductive elements, not only in the conducting circuits (rails, catenary), showed that the proposed "field" approach to active losses is more complex and takes into account losses in locomotives and wagons. Another approach to electromagnetic processes in electric transport systems is presented in paper [25].…”
Section: Overview Of Contributions To This Special Issuementioning
confidence: 99%
“…The complexity of the formation of the load on the traction power supply system is caused by the simultaneous processes of electric locomotives movement and electric drives regulation. Researchers [4] note that the spectral analysis of traction volt ages and currents is the basis for assessing the level of electro magnetic compatibility and quality of power consumption in electric transport systems. Carrying out such an analysis is com plicated by the fact that electric locomotives operate in non stationary dynamic modes.…”
mentioning
confidence: 99%